Neighbourhood disadvantage impacts on pulmonary function in patients with sarcoidosis. Issue 4 (24th October 2022) - Goobie, Gillian C.; Ryerson, Christopher J.; Johannson, Kerri A.; Keil, Spencer; Schikowski, Erin; Khalil, Nasreen; Marcoux, Veronica; Assayag, Deborah; Manganas, Hélène; Fisher, Jolene H.; Kolb, Martin R.J.; Chen, Xiaoping; et al.
Background: This multicentre, international, prospective cohort study evaluated whether patients with pulmonary sarcoidosis living in neighbourhoods with greater material and social disadvantage experience worse clinical outcomes. Methods: The area deprivation index and the Canadian Index of Multiple Deprivation evaluate neighbourhood-level disadvantage in the US and Canada, with higher scores reflecting greater disadvantage. Multivariable linear regression evaluated associations of disadvantage with baseline forced vital capacity (FVC) or diffusing capacity of the lung for carbon monoxide ( D LCO ) and linear mixed effects models for associations with rate of FVC or D LCO decline, and competing hazards models were used for survival analyses in the US cohort, evaluating competing outcomes of death or lung transplantation. Adjustments were made for age at diagnosis, sex, race and smoking history. Results: We included 477 US and 122 Canadian patients with sarcoidosis. Higher disadvantage was not associated with survival or baseline FVC. The highest disadvantage quartile was associated with lower baseline D LCO in the US cohort (β = −6.80, 95% CI −13.16 to −0.44, p=0.04), with similar findings in the Canadian cohort (β = −7.47, 95% CI −20.28 to 5.33, p=0.25); with more rapid decline in FVC and D LCO in the US cohort (FVC β = −0.40, 95% CI −0.70 to −0.11, p=0.007; D LCO β = −0.59, 95% CI −0.95 to −0.23, p=0.001); and with more rapid FVC decline in the Canadian cohort (FVC β = −0.80, 95% CI −1.37 to −0.24, p=0.003). Conclusion: Patients with sarcoidosis living in high disadvantage neighbourhoods experience worse baseline lung function and more rapid lung function decline, highlighting the need for better understanding of how neighbourhood-level factors impact individual patient outcomes. Gre ater neighbourhood disadvantage is associated with worse baseline lung function and more rapid lung function decline in patients with sarcoidosis in both US and Canadian cohorts, highlighting the impact of socioeconomic disparities in this population https://bit.ly/3R8gUuc